The off-axis behavior of a unidirectional fiber-reinforced plastic composite - Kroupa, Tomáš (Materiali in tehnologije, 2008)
Numerical and experimental investigations of the off-axis behavior of a unidirectional fiber-reinforced plastic composite consisting of carbon fibers and an epoxy matrix are presented. Static tensile tests of thin carbon-epoxy composite strips with various fiber directions were performed and simulated using a finite-element program. Pack's action-plane concept (failure criterion) and progressive failure analysis were used for the damage prediction of the tested thin strips. A non-linear stress-strain relation was used for modeling the off-axis behavior. The relation between the tensile force and the displacement in the direction of the loading force and the ultimate tensile force, which caused damage and the ultimate displacement of specimens, were measured and compared with the results of the numerical simulation. The fiber directions of the specimens, measured from the directionof loading, were in the interval 0compositum-90compositum. Good agreement between the experimental results and the numerical simulations was achieved. The non-linear stress-strain relation was verified for the case of along-fiber carbon-epoxy composite loaded with a static tensile loading force.
Keywords: kompoziti; ogljik-epoksi; natezni preizkus; nelinearnost